Florestan Fernandes e o caráter autocrático da burguesia brasileira: uma leitura sobre A revolução burguesa no Brasil - Rosso, Kelem Ghellere [UNESP] (2015)
This work aims to recover the concept of bourgeois autocracy present in the work A Revolução Burguesa no Brasil: ensaio de interpretação sociológica, Florestan Fernandes, for today we start from the assumption of its concept for questioning about the nature of democracy in Brazil. Underlying this hypothesis is that the explanatory potential of contributions on the autocratic character of bourgeois rule in the countries of dependent capitalism are intensified with the intensification of capital's structural crisis of the system. To these reflections, the work is dedicated to the analysis of the main categories for understanding the bourgeois autocracy under Florestan Fernandes. Thus the bourgeois autocracy is understood here as the maximum political expression and synthesis of the contradictions of the type of capitalism here possible, dependent capitalism, which keeps the extreme concentration of wealth and political power present since the colonial period.